Two decades of universal HCR: A bibliometric analysis (2004–2024) - Olaf Ingmar (Health Economics Insights Journal, 2026)
Universal Health Coverage (UHC) is a central target of the Sustainable Development Goals (SDG 3.8) and a defining ambition of contemporary health-systems policy. Although the associated scholarship has expanded rapidly, the intellectual structure of the field has not been comprehensively mapped. This study characterises two decades of UHC research bibliometrically, describing how the field has grown, who has produced it, and how its themes have evolved. We conducted a performance analysis and science mapping of UHC-related documents published between 2004 and 2024, following established bibliometric guidance. The dataset (N = 9,828 journal articles) was retrieved from the OpenAlex scholarly database using an exact-phrase title/abstract query for “universal health coverage”, restricted to journal articles published in 2004–2024. Analyses were implemented in a reproducible Python pipeline and covered annual output and growth; the productivity, citation impact, and international-collaboration structure of countries, journals, authors, and institutions; the most-cited documents; and concept co-occurrence and thematic structure. The field displays sustained, accelerating growth. Output is concentrated among a small set of high-income countries, global-health and health-policy journals, and a core of prolific authors and institutions. International collaboration is extensive but asymmetric, and the thematic landscape spans health financing, financial risk protection, primary health care, equity, and health-systems strengthening, with newer clusters around quality of care, service-coverage measurement, and the SDGs. UHC research is a maturing, policy-facing, and highly international field whose geography of knowledge production raises equity considerations relevant to its future agenda. Keywords: universal health coverage; bibliometric analysis; science mapping; health systems; health financing; Sustainable Development Goals